Study protocol for a modified antenatal care program for pregnant women with a low risk for adverse outcomes-a stepped wedge cluster non-inferiority randomized trial - Valerie Stålberg; Barbro Krevers; Lovisa Lingetun; Therese Eriksson; Ann Josefsson; Caroline Lilliecreutz (BMC, 2022)
Abstract Background It is crucial to provide care based on individual needs. Swedish health care is obliged to give care on equal conditions for the entire population. The person with the greatest need should be given the most care, and the health care system should strive to be cost-efficient. Medical and technical advances have been significant during the last decades and the recent Covid-19 pandemic has caused a shift in health care, from in-person visits to virtual visits. The majority of pregnant women with a low risk assessment have an uncomplicated antenatal course without adverse events. These women probably receive excessive and unnecessary antenatal care. This study will investigate if an antenatal care program for healthy pregnant women with a low risk for adverse outcomes could be safely monitored with fewer in-person visits to a midwife, and with some of them replaced by virtual visits. Methods This is a non-inferiority trial where a stepped wedge cluster randomized controlled design will be used. Data collection includes register data and questionnaires that concern antenatal, obstetric and neonatal outcomes, patient- and caregiver-reported experiences, healthcare-economy, and implementation aspects. The modified antenatal care (MAC) study is performed in parts of the southeast of Sweden, which has approximately 8200 childbirths annually. At the start of the study, all antenatal care centers included in the study will use the same standard antenatal care (SAC) program. In the MAC program the in-person visits to a midwife will be reduced to four instead of eight, with two additional virtual meetings compared with the SAC program. Discussion This presented study protocol is informed by research knowledge. The protocol is expected to provide a good structure for future studies on changed antenatal care programs that introduce virtual visits for healthy pregnant women with a low risk for adverse outcomes, without risking quality, safety, and increased costs. Trial registration The study is registered the 21th of April 2021 in the ISRCTN registry with trial ID: ISRCTN14422582 , retrospectively registered.